EVALUATING THE EFFECTS OF ADOPTION OF IMPROVED PROCESSING TECHNOLOGIES ON TECHNICAL EFFICIENCY OF PALM OIL PROCESSORS IN OGUN STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Although Nigeria is ranked third among palm oil producers globally, her production still falls short of local demand, indicating a gap in processing efficiency. This study examined the effect of adoption of improved processing technologies on technical efficiency of rural processors. The study is based on a primary dataset collected from 80 palm oil processors who were selected through multistage random sampling from Ipokia and Ado-Odo Ota Local Government Areas of Ogun State, Nigeria. Data were analysed with budgetary analysis and stochastic frontier analysis to estimate the profitability and technical efficiency of oil palm processing enterprise respectively. An average processor is capable of realizing 36 kobo as gain on every naira invested in the business. The results showed that the enterprise yielded profitable returns to the processors. The mean technical efficiency (TE) 0.95 indicates that 95% of the respondents are efficient and 5% inefficient. Quantity of palm fruits, quantity of water, and transportation cost were the crucial factors that contributed to the TE of oil palm processors while age, membership of association and adoption of oil clarifier significantly affect their technical inefficiency. The study recommends proper training on palm oil processing towards usage of the desired technology to attain capacity building
Keywords: Adoption, Palm oil, Stochastic Frontier Analysis, Technical Efficiency